2021
DOI: 10.1002/er.7208
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis and optimization of the combined supercritical carbon dioxide Brayton cycle and organic Rankine cycle‐based nuclear hydrogen production system

Abstract: The Supercritical Carbon Dioxide Brayton Cycle (SCBC) with high efficiency is a very promising thermodynamic cycle to replace the Steam Rankine Cycle (SRC) as the power cycle of a Nuclear Hydrogen Production (NHP) system. However, detailed research on the NHP system using SCBC as a power cycle has not been carried out so far and the system's thermodynamic characteristics are not well known. To fill this research gap, three promising very high-temperature gas-cooled reactor and copper-chlorine cycle-based NHP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Simple design, compact layout, high thermal efficiency, acceptable cleanliness, and potential capital cost savings are the distinct advantages of this cycle [1]. Thus, it seems that the SCO 2 Brayton cycle can be used as an attractive thermal-topower system in future generations of fossil-fired plants as well as other novel plants working with waste heat recovery, concentrated solar, and nuclear power sources [2].…”
Section: Introductionmentioning
confidence: 99%
“…Simple design, compact layout, high thermal efficiency, acceptable cleanliness, and potential capital cost savings are the distinct advantages of this cycle [1]. Thus, it seems that the SCO 2 Brayton cycle can be used as an attractive thermal-topower system in future generations of fossil-fired plants as well as other novel plants working with waste heat recovery, concentrated solar, and nuclear power sources [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, from the perspective of long-term development, these methods are no longer feasible because a huge amount of fossil fuels and electricity are consumed during the hydrogen production process, causing significant carbon emissions. 6 Therefore, several advanced thermochemical water-splitting cycles including the iodine-sulfur (I-S) cycle 7 and the copper-chlorine (Cu-Cl) cycle 8 are proposed and are currently being studied actively by many researchers as these cycles are very promising to achieve the large-scale carbon-free hydrogen production when they are coupled with a solar heliostat system 9 or a generation IV nuclear reactor system. 10 The I-S cycle developed by General Atomics in the 1970s is one of the most famous thermochemical watersplitting cycles and has been widely studied by many countries, 11 such as France, 12 America, 13 Japan, 14 China, 15 and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainable index of the S-CO 2 cycle/subcritical ORC is 1.54, while it is 1.57 for the S-CO 2 cycle/transcritical ORC. Wang et al [19] contrasted three cycles for a nuclear hydrogen production (NHP) system: steam Rankine cycle (SRC), S-CO 2 and combined S-CO 2 /ORC. They showed that, when the inlet temperatures of the reactor in the S-CO 2 cycle are 400 • C and 587 • C, the first law efficiency of the S-CO 2 cycle varies from 27.5% to 31.0% and 27.5% to 36.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%